Development of 1 kW‐class Ammonia‐fueled Solid Oxide Fuel Cell Stack. Issue 1 (22nd January 2020) - Kishimoto, M.; Muroyama, H.; Suzuki, S.; Saito, M.; Koide, T.; Takahashi, Y.; Horiuchi, T.; Yamasaki, H.; Matsumoto, S.; Kubo, H.; Takahashi, N.; Okabe, A.; et al.
Abstract: Power generation performance and long‐term durability of ammonia‐fueled solid oxide fuel cell (SOFC) systems are investigated with SOFC stacks consisting of 30 planar anode‐supported cells. SOFC systems with three different operation modes are employed: direct ammonia, external decomposition and autothermal decomposition. A novel BaO/Ni/Sm2 O3 /MgO catalyst is newly developed for the external ammonia cracker, whereas a Co‐Ce‐Zr composite oxide catalyst is used for the autothermal ammonia cracker. Initial performance measurement and 1, 000 h long‐term durability test of the stacks are conducted. The stack fueled with direct ammonia achieves 1 kW power output with 52% direct current (DC) electrical efficiency; a slight decrease in its performance compared with the stack with the mixture fuel of hydrogen and nitrogen is attributed to the decrease in the stack temperature caused by the endothermic ammonia decomposition reaction. The external ammonia cracker helps to maintain the stack temperature, improving the initial performance of the stack. The stack performance with the autothermal ammonia cracker is also comparable to those with the other operation modes. It is also demonstrated that the stacks fueled with ammonia have excellent stability during the long‐term tests and 57% energy conversion efficiency at ca. 700 W electrical output is achieved with the external ammonia cracker.